A Preliminary Checklist of the Orchid Bees (Hymenoptera: Apidae: Euglossini) of Ecuador - Pablo S. Padrón; David W. Roubik; Ruben P. Picón (Psyche: A Journal of Entomology)
A checklist of Euglossini in Ecuador is given, including all currently described, valid species collected until 2018. The list has been assembled from museum records, fieldwork cited herein, and literature. The former species lists are nearly doubled here, with 1 Aglae, 23 Eufriesea, 68 Euglossa, 18 Eulaema, and 5 Exaerete, 115 in total with >50 new records for the country. Distribution and collection data are included, and some doubtful species are discussed. The Amazon region is the most species rich area but not necessarily a natural pattern, perhaps due to uneven sampling effort across the country. Southern Ecuador is relatively little sampled.